2010
DOI: 10.1038/ijo.2010.213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lupin-enriched foods on body composition and cardiovascular disease risk factors: a 12-month randomized controlled weight loss trial

Abstract: Background: Regular consumption of diets with increased protein or fibre intakes may benefit body weight and composition and cardiovascular disease risk factors. Lupin flour is a novel food ingredient high in protein and fibre. Objective: To investigate the effects of a lupin-enriched diet, during and following energy restriction, on body weight and composition and cardiovascular disease risk factors in overweight individuals. Design: Participants (n ¼ 131) were recruited to a 12-month parallel-design trial. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 46 publications
4
76
4
2
Order By: Relevance
“…The effect between the intervention and the control diets did not differ significantly (mean difference −0.09 mmol/L, 95% CI −0.19 to 0.00 mmol/L); however, inter-study heterogeneity was very high (I 2 = 98%). Sensitivity analy- Zhang et al 32 ses showed that the pooled effect size became significant when any of the 6 trials that favoured the effect of the control diet 6,8,22,23,26,38 was removed. The use of a correlation coefficient of 0.25 did not alter conclusions, but a correlation coefficient of 0.75 resulted in a significant reduction in non-HDL cholesterol favouring the dietary pulse intervention.…”
Section: 29mentioning
confidence: 99%
“…The effect between the intervention and the control diets did not differ significantly (mean difference −0.09 mmol/L, 95% CI −0.19 to 0.00 mmol/L); however, inter-study heterogeneity was very high (I 2 = 98%). Sensitivity analy- Zhang et al 32 ses showed that the pooled effect size became significant when any of the 6 trials that favoured the effect of the control diet 6,8,22,23,26,38 was removed. The use of a correlation coefficient of 0.25 did not alter conclusions, but a correlation coefficient of 0.75 resulted in a significant reduction in non-HDL cholesterol favouring the dietary pulse intervention.…”
Section: 29mentioning
confidence: 99%
“…The others are blind studies on model foods containing whole kernel flour: lupin bread in the former (Hodgson, Lee, Puddey, Sipsas, Ackland, Beilin, et al, 2010) and a portfolio of different lupin foods in the latter (Belski, Mori, Puddey, Sipsas, Woodman, Ackland, et al, 2011). Both studies, involving only subjects with normal or borderline initial cholesterol levels, were essentially inactive on cholesterol.…”
Section: Human Studiesmentioning
confidence: 99%
“…Moreover, two long-term randomized controlled studies showed that the consumption of foods supplemented with narrow-leaf lupin flour produced small but statistically significant decreases in blood pressure versus the control foods (Belski, et al, 2011;Ya P. Lee, Mori, Puddey, Sipsas, Ackland, Beilin, et al, 2009). Overweight and obese subjects (88) consumed white wheat bread (control group) or a lupin flour-enriched bread (treated group) for 16 weeks.…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Narrow-leaf Lupin is currently under widespread cultivation in Europe [2], but most commonly found in Mediterranean countries. NLL is getting more and more recognition as a potential human healthy food with specific nutritional attributes [3] associated with high protein and dietary fibre content [4]. Additionally it has potential healthy pharmaceutical attributes since it plays a role similar to the hypoglycaemic drug metformin which is used for the treatment of type 2 diabetes (T2D), particularly in overweight and obese people [5].…”
Section: Introductionmentioning
confidence: 99%